Optimizing the Performance of the Quality Assurance Committee in the Implementation of Education and Training BPSDM Papua Province - Yohanes, Sewo (Budapest International Research and Critics University, 2021)
The purpose of this study is to find out and analyze the role of the Quality Assurance Committee in the implementation of education and training at BPSDM Papua Province. 2) to find out and analyze the Performance Optimization of the Quality Assurance Committee in the implementation of Education and Training at BPSDM Papua Province. The research method used is descriptive analysis research, which is to provide data that is as accurate as possible about humans, circumstances or other symptoms, especially to reinforce hypotheses so that they can assist in strengthening old theories or within the framework of developing new theories. The results of this study are the role of the Papua Province BPSDM Quality Assurance Committee plays an important role in the education and training implementation process because the role of KPM can help make standard standards in conducting education and training starting from the planning, evaluation and quality quality stages, besides that KPM can make post-training instruments and implement so that BPSDM Papua Province as the organizer of the education and training has data related to the quality of graduates who have attended the training. So it can be concluded that the role of the Papua Province BPSDM Quality Assurance Committee plays an important role in providing education, training and implementing it so that the Papua Province BPSDM as the education and training provider has data related to the quality of graduates participating in the training. Optimizing the performance of KPM BPSDM Papua Province can be done through several environmental aspects, namely, the social environment, the political and legal environment, the labor environment and the technical environment. KPM BPSDM Papua Province as a team that carries out quality control and assurance functions must carry out its duties and responsibilities as well as possible and professionally so that BPSDM Papua Province can feel the existence of KPM.